Analisis Kadar Asam Retinoat dalam Krim Pemutih Malam di Kota Malang - Fendi Yoga Wardana; Yunida Senja Lestari; Rakhmadani Gadis Aprilianti (LPPMKI - AKAFARMA AKFAR PIM, 2022)
Whitening cream is a product that is used on the outside of the body to lighten or change the color of the skin. Whitening cream contains chemicals that are harmful to the skin, such as mercury, hydroquinone, and retinoic acid. Retinoic acid belongs to a group of drugs that are prohibited because it can cause dry skin, burning and teratogenicity. Therefore, it is necessary to analyze the retinoic acid in whitening cream. This study aims to determine the content of retinoic acid in night whitening cream. The samples in this study were 5 night whitening cream products marketed in Malang. Qualitative test of retinoic acid was performed by Thin Layer Chromatography (TLC) with silica gel 60F 254 nm as a stationary phase and n-hexane: acetone (6:4) as a mobile phase, and quantitative test using UV-Vis spectrophotometry. The observation result on TLC shows dark blue spots when viewed under UV light at 254 nm with Rf values for samples B, D, and E of 0.487; sample C of 0.425; while the Rf value of the comparison standard is 0.500. The quantitative test indicates 4 samples of night whitening cream contain retinoic acid; 0.165% in sample B, 0.060% in sample C, 0.125% in sample D, and 0.151% in sample E. In conclusion, samples B, C, D and E do not meet the BPOM requirements because they are sold freely without a doctor's supervision.